The Northeast Asian Regional Security Complex: Japan-Russia Defense Relations - Rinna, Anthony V. (WILAYAH: The International Journal of East Asian Studies, 2016)
This paper addresses Japan-Russia defense relations in the context of Japan's defense policy shift regarding the reinterpretation of the Japanese constitution's Article 9, Russia's recalibration of its military forces in the Asia-Pacific, and the rise of Chinese military power in Northeast Asia. It argues that as Northeast Asia comprises a "regional security complex", the security relationship between Japan and Russia, is not solely contingent upon Moscow and Tokyo's handling of bilateral affairs. Rather, external factors that involve both Japan and Russia separately also affect this bilateral security relationship. Despite the Japanese and Russian governments' efforts toward improving bilateral defense relations in light of the Kuril Islands/Northern Territories dispute, Moscow and Tokyo's respective defense policies in response to the rise of China's military prowess in Northeast Asia also affect Japan-Russia defense relations. Specifically, Japan and Russia's buildup of their navies in order to counter the rise of China's maritime prowess may also cause military tensions between Moscow and Tokyo.